MACROECONOMIC DYNAMICS AND THE ROLE OF MARKET POWER. THE CASE OF ITALY - MONDOLO, Jasmine (Theoretical and Practical Research in Economic Fields; Vol 13 No 2 (2022): TPREF, Volume XIII, Issue 2(26), Winter 2022DO - 10.14505/tpref.v13.2(26).03, 2022)
In recent years, the US and other advanced countries have experienced macroeconomic dynamics which raise some concerns and which, according to the literature, are at least partly attributable to a rise in product market power. This study mainly aims to understand how Italy performs in terms of five relevant economic variables (i.e., domestic investment rate, labour share, labour force participation, wage inequality and economic dynamism), and whether firms’ markups are on the rise. The picture that emerges is mixed, and the negative performance in terms of business dynamism and wage dispersion may be ascribable to an increase in product market power. The firm-level analysis of the Italian manufacturing sector for the years 2011-2018, which complements previous empirical analysis on product market power in this country and accounts for labour market power as well, reveals an increment in the average markup which, however, is not particularly pronounced and unsettling, and which is preceded by a period of steady decline. Moreover, this trend is accompanied by a more remarkable increase in the workers’ labour market power, which helps explain the modest growth in the revenue-based labour share observed during the same period.